As aglomerações produtivas de calçados, folheados e de jóias do CRAJUBAR (CE): formação, produção, trabalho, implicações socioespaciais - Cordeiro, Rosemary de Matos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The overall objective of this thesis is to analyze the general socio-economic and spatial aspects of industrial activity in productive agglomerations of shoes and jewelry plated in Juazeiro, Crato and Barbalha; their productive and recent economic dynamic structures, the intervening factors in its evolution and its current situation, assessing their socio-spatial implications. The nuclear argument is that, given the presence of a set of endogenous factors that characterize the CRAJUBAR, represented by religiosity created around the Padre Cicero figure; for growth, due to population growth, with local market for both religious items as to basic necessities; the appearance on the place of a tacit knowledge, focused on the production of shoes and jewelery diverse, widespread among the sites; by the resulting creation of a historical and cultural tradition founded in the craft/industrial work; a strong entrepreneurship by local actors, can be recognized and emphasized the occurrence and stay until the present day in the CRAJUBAR region, of significant productive agglomerations of footwear and jewelry plated. They appear with sufficient economic dynamism to provide a satisfactory economic expansion to the area, with reasonable offer of employment and income, despite the coexistence of a formal sector and other informal, very significant, allowing the coexistence of two worlds, expressed by the presence of a sector that is modernizing and the continuity and maintenance of archaic production in the two segments studied. The study adopted as methodological approach the literature and field research, being interviewed a total of 95 entrepreneurs in the footwear sector (among formal and informal producers) and 46 productive actors on the jewelry and plated sector (also formal and informal) aside from supporting institutions. Some of the observed results were: existence of productive linkages in both segments derived from the social and technical ...

O objetivo geral desta tese é analisar os aspectos socioeconômicos e espaciais gerais da atividade industrial nas aglomerações produtivas de calçados e folheados em Juazeiro do Norte, Crato e Barbalha; bem como suas estruturas produtivas e dinâmicas econômicas recentes, os fatores intervenientes em sua evolução e sua situação atual, avaliando suas implicações socioespaciais. A argumentação nuclear é que, dada a presença de um conjunto de fatores endógenos que caracterizam o CRAJUBAR, representados pela religiosidade criada em torno da figura do Padre Cícero; pelo crescimento, devido à expansão populacional, de mercado local, tanto para artigos religiosos como para bens de primeira necessidade; pelo surgimento, no local, de um conhecimento tácito, voltado para a produção de calçados e de ourivesaria diversa, disseminado entre os locais; pela decorrente criação de uma tradição histórico-cultural, fundada no trabalho artesanal/industrial; um forte empreendedorismo por parte dos atores locais, podem ser reconhecidos e enfatizados a ocorrência e a permanência, até os dias atuais, na região do CRAJUBAR, de significativas aglomerações produtivas de calçados e de folheados. Elas se apresentam com dinamismo econômico suficiente para propiciar uma satisfatória expansão econômica para a área, com razoável oferta de emprego e renda, apesar da coexistência de um setor formal e de outro informal, bastante significativo, propiciando a convivência entre dois mundos, expressos pela presença de um setor que se moderniza e pela continuidade e manutenção da produção arcaica, nos dois segmentos estudados. O estudo adotou como procedimento metodológico as pesquisas bibliográfica e de campo, sendo entrevistados um total de 95 empreendedores do setor de calçados (dentre os quais, produtores formais e informais), e 46 atores produtivos do setor de folheados e joias (também formais e informais), afora...
Keywords: Economic geography; Geografia econômica; Calçados - Indústria - Aspectos sociais; Calçados - Indústria - Aspectos econômicos; Joias - Indústria - Aspectos sociais; Joias - Indústria - Aspectos econômicos; Ourivesaria; Juazeiro do Norte (CE); Crato (CE); Barbalha (CE)